Prevalence, Diagnosis, and Treatment Rates of Mood Disorders among Opioid Users under Criminal Justice Supervision. (29th July 2018) - Mbaba, Mary; Brown, Shan-Estelle; Wooditch, Alese; Kiss, Marissa; Murphy, Amy; Kumari, Suneeta; Taxman, Faye; Altice, Frederick; Lawson, William B.; Springer, Sandra A.
ABSTRACT: Background : Individuals involved in the criminal justice system have disproportionately high rates of psychiatric disorders when compared to the general U.S. population. If left untreated, the likelihood of subsequent arrest increases and risk for adverse health consequences is great, particularly among opioid users. Objectives : To explore the prevalence, characteristics, and treatment of mood disorders among justice involved opioid-dependent populations. Methods : The current study enrolled 258 treatment-seeking opioid-dependent individuals under community-based criminal justice supervision (e.g., probation, parole) screened from the larger parent study, Project STRIDE, a seek/test/treat randomized control trial (RCT) examining HIV and opioid use treatment. During baseline, individuals were screened for depression using the Patient Health Questionnaire-9 (PHQ-9) and screened for bipolar disorder using the Mood Disorder Questionnaire (MDQ) tool. Results : Overall, 78 (30%) participants screened positive for moderate to severe depression and 54 (21%) screened positive for bipolar disorder. Participants self-reported mood disorders at higher rates than they screened positive for these conditions. Participants screening positive for these conditions experienced significantly greater family, legal, and medical problems on the Addiction Severity Index-Lite (ASI-Lite) than those who did not screen positive. Incidence of a lifetime suicide attempt was found to be associated with a positive screen for both mood disorders. Prescribed psychotropic treatment utilization was similar among those who screened positive for depression or bipolar disorder with approximately 38% reporting taking medication. Importance : Findings suggest universal mood disorder screening to improve comprehensive psychiatric care and treatment of opioid-dependent justice-involved individuals.